Trends in orphan drug use and spending among children and adolescents during 2010–2020 in Korea - Oh, Jung Yeon; Lee, Jin Yong; Kim, Dong-Sook (Frontiers in Pharmacology, 2022)
Background: Since 2014 in Korea, the Ministry of Food and Drug Safety has designated orphan drugs (ODs) for the treatment of rare diseases. This study investigated the market share and 20 most frequently prescribed therapeutic subgroups of ODs among children and adolescents in Korea. Methods: This study referenced the Korean national health insurance claims database from January 2010 through December 2020. The outcome measures were the number of prescriptions and expenditures on ODs. Results: Among children aged 0-12 years, the number of patients using ODs increased from 11,264 in 2010 to 14,017 in 2020. The expenditures on ODs and their proportion of total pharmaceutical expenditures also tripled from 13.3 million USD (1.2%) in 2010 to 46.4 million USD (6.2%) in 2020. Among the overall population and adolescents aged 13-17 years, the percentage of total pharmaceutical expenditures for ODs increased from 0.4% in 2010 to 3.2% in 2020 and from 2.1% in 2010 to 11.2% in 2020, respectively. The highest numbers and spending of child patients were for H01 (pituitary and hypothalamic hormones and analogues, 44,839) and A16 (other alimentary tract and metabolism products, 160 million USD). The individual ODs with the highest spending were A16AB09 (idursulfase, 82.4 million USD) and M09AX07 (nusinersen, 36.2 million USD). Conclusion: Although the market size of ODs remained small in Korea, both the approved ODs and the proportion of total pharmaceutical expenditure by ODs have increased. Additional policies related to designation and reimbursement should be put in place to ensure timely access to ODs.